EMPOWERING LESOTHO'S TOMORROW: YOUTH-DRIVEN INNOVATION IN PREVENTIVE HEALTHCARE (Proceedings of the Global Public Health Conference, 2024)
This study is rooted in the imperative to incorporate the voices of youth into the development of programmes and policies, in Lesotho. The aim was to understand the health and well-being challenges they face and to highlight the need for innovative, preventive, and participatory interventions, which include their unique perspectives and contributions. The research involved 180 children, both boys and girls, from various ecological zones, using a qualitative approach to gather detailed insights. Data were collected using Participatory Learning Approach tools, including Social and Resource Mapping, Cause and Effect Analysis, which were supplemented by Key Informant Interviews. The study team also conducted 18 Focus Group Discussions, aimed to gain a more comprehensive understanding of the children’s perspectives, experiences and needs. The study unveils several health challenges that young people in Lesotho face, including malnutrition, limited access to healthcare, and gender-based violence. Despite these difficulties, the stories shared by the participants show a strong sense of resilience and a keen desire to be actively involved in policymaking and interventions related to their health and well-being. The findings have significant implications. They provide a framework for health professionals and policymakers to incorporate the perspectives of children and youth into preventive health strategies. Additionally, the study highlights the need for a shift in public health discussions, advocating for inclusive policy development that considers the unique needs and rights of young populations. These insights, though specific to Lesotho, could be valuable in similar contexts.
Keywords: preventive healthcare; child participation; qualitative research; Lesotho; public health policy